Му-му. Умереть до расстрела: роман / Андрей Воронин, Максим Гарин - Воронин Андрей Николаевич (Харвест, 1999)
Экземпляры: ЧЗ (20181112) / Инвентарный номер: 34649 / Цена: 32 / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: В 76 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44